Normal reference values of strength in pelvic floor muscle of women: a descriptive and inferential study - Chevalier, Francine; Fernandez-Lao, Carolina; Cuesta-Vargas, Antonio (BMC Springer Nature, 2014)
Background: To describe the clinical, functional and quality of life characteristics in women with Stress Urinary Incontinence (SUI). In addition, to analyse the relationship between the variables reported by the patients and those informed by the clinicians, and the relationship between instrumented variables and the manual pelvic floor strength assessment. Methods: Two hundred and eighteen women participated in this observational, analytical study. An interview about Urinary Incontinence and the quality of life questionnaires (EuroQoL-5D and SF-12) were developed as outcomes reported by the patients. Manual muscle testing and perineometry as outcomes informed by the clinician were assessed. Descriptive and correlation analysis were carried out. Results: The average age of the subjects was (39.93 ± 12.27 years), (24.49 ± 3.54 BMI). The strength evaluated by manual testing of the right levator ani muscles was 7.79 ± 2.88, the strength of left levator ani muscles was 7.51 ± 2.91 and the strength assessed with the perineometer was 7.64 ± 2.55. A positive correlation was found between manual muscle testing and perineometry of the pelvic floor muscles (p < .001). No correlation was found between outcomes of quality of life reported by the patients and outcomes of functional capacity informed by the physiotherapist. Conclusion: A stratification of the strength of pelvic floor muscles in a normal distribution of a large sample of women with SUI was done, which provided the clinic with a baseline. There is a relationship between the strength of the pelvic muscles assessed manually and that obtained by a perineometer in women with SUI. There was no relationship between these values of strength and quality of life perceived.
Keywords: Suelo pélvico; Pelvic floor muscles; Stress urinary incontinence; Normal reference values; Scoring measures